From clerics to lyricists: medieval don-juanism and monastic pickup - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The interpretation of love is considered in the context of the lyric poetry of the Ovidian Renaissance. The focus is on such issues as the rethinking of traditional issues of lyric poetry, new themes and lyric plots of Ovidian poets, the influence of their work on the orthodox-Christian context and the reverse influence of this context on their mentality, the role of the Ovidian Renaissance in the legitimacy of love in the context of medieval culture.